Porous material for heat insulation of drilling shaft as well as preparation method and application of porous material

By using spherical porous materials prepared by natural ore and industrial waste, combined with rotary granulation and nanospray technology, porous ceramic granules with multi-stage cell cavity structure were prepared and their surfaces were modified, which solved the problem of excessive temperature of deep drilling wellbores and achieved efficient wellbore insulation.

CN119638481AActive Publication Date: 2025-03-18CHINA UNIV OF PETROLEUM (EAST CHINA)

Patent Information

Application Number
CN202411791450.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-03-18
Estimated Expiration
2044-12-06

AI Technical Summary

Technical Problem

The high temperature of the deep drilling wellbore leads to accidents such as drilling fluid failure, drilling tool damage and well leakage. The existing porous ceramic particles are large in size, high thermal conductivity, and surface characteristics cannot be adsorbed on the well wall, which cannot effectively reduce the wellbore temperature.

Method used

Spherical porous materials are prepared by natural ore and industrial waste, and porous ceramic granules with multi-stage cell cavity structures are prepared through rotary granulation and nanospray assistive technology, and their surfaces are modified by anionic and cationic, so that they can be adsorbed to the well wall for heat insulation.

Benefits of technology

The ultrafine particle size and high porosity of porous materials are achieved, with low thermal conductivity and good thermal insulation effect. It can effectively reduce the wellbore temperature and prevent the ceramic particles from being screened by the solid-liquid separation device, which is conducive to multiple recycling.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention provides a porous material for heat insulation of a drilling shaft and a preparation method and application thereof, and belongs to the technical field of oilfield chemistry. The preparation method of the porous material comprises the following steps: fully and uniformly mixing ceramsite powder and a pore-forming agent; the colloidal solution is used as a binder, and porous ceramsite is obtained through granulation and heat treatment; the preparation method comprises the following steps: fully dispersing porous ceramsite, an anionic monomer and a cationic monomer in deionized water, adding an initiator, reacting, washing, and drying. The porous material adopts natural ores and industrial wastes as raw materials, and the raw materials are cheap, easy to obtain, low in cost, green and environment-friendly. The porous material is applied to shaft heat insulation and can prevent ceramsite from being screened out by a solid-liquid separation device, and repeated recycling is facilitated; a large number of micron-scale and nano-scale pores are formed in the porous material, the heat conductivity coefficient is low, and the heat insulation effect is good; the surface of the porous material contains abundant anion and cation groups, and the porous material can be adsorbed on the shaft wall for effective and stable heat insulation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of oilfield chemistry, and particularly relates to a porous material for heat insulation of a drilling wellbore and a preparation method and application thereof. Background Art

[0002] When the drilling depth exceeds 8000m, the wellbore temperature has reached over 200℃. The high temperature causes the failure of drilling fluid, damage to drilling tools and failure of logging equipment while drilling, making drilling very difficult. In more serious cases, major accidents such as well leakage, well collapse and blowout may occur, causing incalculable economic losses. Therefore, reducing the wellbore temperature is crucial for the development of deep oil and gas.

[0003] The temperature of the wellbore mainly comes from the heat transfer of high-temperature strata. The high temperature of the deep strata transfers heat to the wellbore wall, and then to the drilling fluid and drill pipe in turn. By establishing an insulating layer on the wellbore wall, it is expected to reduce the heat transfer from the stratum to the wellbore, thereby reducing the wellbore temperature. Porous ceramsite is a lightweight porous material made of clay, shale or industrial waste. It has the advantages of easy processing, low cost, high strength and low thermal conductivity. It is widely used in construction, gardening and other fields. However, the size of existing porous ceramsite is too large, it is easy to be screened out by the solid-liquid separation device, and it cannot be recycled many times; the thermal conductivity is too high, and the insulation effect needs to be improved; its surface characteristics cannot be adsorbed on the wellbore rock for insulation, and it is difficult to modify. For example, the invention patent CN118495983A discloses a Yunnan laterite-based composite porous ceramsite and its preparation method. Through a simple process, ceramsite with high specific surface area, high porosity and high strength is prepared, and it also has nanopores. However, the size of the ceramsite is very large, 4.5-7 mm, and it has not been surface modified, so it cannot be used for wellbore insulation. Invention patent CN114276084A discloses a heat-insulating ceramsite wallboard, which discloses the preparation of modified ceramsite, first activating the surface of the ceramsite with hexadecyltrimethylammonium bromide, so that the surface of the ceramsite absorbs periclase powder, and finally forms a silicon dioxide layer on the outside with ethyl orthosilicate. However, due to the size constraints of the modified ceramsite and the high thermal conductivity, it cannot be used in the field of wellbore insulation.

[0004] Therefore, the problem of drilling difficulties caused by ultra-high wellbore temperature has not been solved, and there is an urgent need to develop new technologies to reduce the wellbore temperature. Summary of the invention

[0005] In view of the deficiencies in the prior art, the present invention provides a porous material for drilling wellbore insulation and a preparation method and application thereof. The porous material of the present invention uses natural ores and industrial waste as raw materials, and the raw materials are cheap and easy to obtain, low in cost, and green and environmentally friendly. The size of the porous material of the present invention can be reduced to below 100 μm, and its application in wellbore insulation can prevent ceramsite from being screened out by a solid-liquid separation device, which is conducive to multiple recycling; the porous material has a large number of micron and nanometer pores inside, low thermal conductivity, and good insulation effect; the surface of the porous material contains rich anion and cationic groups, which can be adsorbed on the wellbore wall for effective and stable insulation.

[0006] The technical solution of the present invention is as follows: A porous material for thermal insulation of a drilling wellbore, wherein the porous material is a spherical structure, has a thermal conductivity of 0.03-0.07 W / mk, a porosity of 80-95%, and a compressive strength of 1-3 MPa; the porous material has a multi-level cell structure, and a pore size of 0.01-20 μm; and the surface of the porous material has anionic and cationic groups.

[0007] Preferably according to the present invention, the porous material is a spherical structure, with a thermal conductivity of 0.038 to 0.048 W / mk, a porosity of 82 to 88%, and a compressive strength of 1.2 to 2.3 MPa; the porous material has a multi-level cell structure with a pore size of 0.01 to 13 μm; and the surface of the porous material carries anionic and cationic groups.

[0008] The method for preparing the porous material for drilling wellbore insulation comprises the following steps: (1) Fully mixing ceramsite powder and pore-forming agent to obtain mixed powder; using colloidal solution as a binder, granulating to obtain ceramsite microspheres; and then heat treating to obtain porous ceramsite; The ceramsite powder is one or a combination of two or more of clay, shale powder, fly ash, coal gangue or iron tailings; the pore former is a combination of micron particles and nanoparticles, the micron particles are polypropylene, polyethylene or polystyrene micron particles, and the nanoparticles are polypropylene, polyethylene or polystyrene nanoparticles; the colloidal solution is one or a combination of two or more of polyvinyl alcohol aqueous solution, polyacrylamide aqueous solution or polyethylene glycol aqueous solution; (2) fully dispersing porous ceramsite, anionic monomers, and cationic monomers in deionized water, adding an initiator, reacting, and then washing and drying to obtain a porous material for drilling wellbore insulation; The anionic monomer is one or a combination of two or more selected from 2-acrylamido-2-methylpropanesulfonic acid, styrenesulfonate, ethylenesulfonate, propylenesulfonate, acrylic acid, methacrylic acid or hydroxyethylacrylic acid; the cationic monomer is one or a combination of two or more selected from dimethyldiallylammonium chloride, polyacrylammonium or polyquaternary ammonium salt; and the initiator is one or a combination of two or more selected from ammonium persulfate, sodium bisulfite or azobisisobutylimidazoline hydrochloride.

[0009] Preferably, according to the present invention, in step (1), the ceramsite powder is a combination of fly ash and coal gangue; wherein the mass ratio of fly ash to coal gangue is 1:0.5-1.

[0010] Preferably, according to the present invention, in step (1), the particle size of the ceramsite powder is 0.5-20 μm, preferably 5-12 μm.

[0011] Preferably, in step (1), in the pore-forming agent, the particle size of the micron particles is 6-13 μm, and the particle size of the nanoparticles is 100-500 nm; the mass ratio of the micron particles to the nanoparticles is 2-4:1, preferably 3:1.

[0012] Preferably, according to the present invention, in step (1), the mass ratio of ceramsite powder to pore-forming agent is 3.75-5:1.

[0013] Preferably, according to the present invention, in step (1), the mixing of the ceramsite powder and the pore-forming agent is carried out in a round pot granulator.

[0014] Preferably, according to the present invention, in step (1), the concentration of the colloidal solution is 0.1-0.8 wt %, preferably 0.5 wt %.

[0015] Preferably, according to the present invention, in step (1), the mass ratio of the mixed powder to the colloidal solution is 1:0.001-0.1.

[0016] Preferably, in step (1), granulation is carried out in a round pot granulator; the mixed powder is rotated in the round pot granulator, and during the rotation, a colloidal solution is sprayed onto the surface of the mixed powder with a nano sprayer, and under the action of gravity and rotation, the mixed powder forms agglomerated micron balls, which are dried to obtain ceramsite microballs; wherein the rotation speed of the round pot granulator is 10 to 200 r / min, the rotation time is 2 to 10 min, and the spraying speed of the nano sprayer is 30 to 1000 ml / min.

[0017] Preferably, in step (1), the heat treatment temperature is 1000-1500° C., the heat treatment time is 2-10 h, and the heat treatment atmosphere is air.

[0018] Preferably according to the present invention, in step (2), the mass ratio of porous ceramsite, anionic monomer, cationic monomer, initiator and deionized water is 1: (0.01-0.1): (0.005-0.1): (0.005-0.01): (0.5-3), preferably 1: 0.05: 0.05: 0.005: 1.

[0019] Preferably, according to the present invention, in step (2), the initiator is in the form of an initiator aqueous solution, and the concentration of the initiator aqueous solution is 0.5 to 5 wt %.

[0020] Preferably, in step (2), the reaction temperature is 20-80°C, preferably 60-80°C, the reaction time is 6-12h, and the reaction is carried out in the absence of oxygen, under protective gas protection and under stirring; preferably, the protective gas is nitrogen or argon.

[0021] Preferably according to the present invention, in step (2), washing is performed using deionized water.

[0022] The above-mentioned porous material for drilling wellbore insulation is used as a thermal insulation material for ultra-deep drilling wellbore insulation.

[0023] Preferably according to the present invention, the ultra-deep layer is a layer with a depth greater than or equal to 8000m.

[0024] The technical features and beneficial effects of the present invention are as follows: (1) The present invention uses natural ores and industrial waste as raw materials. The raw materials are cheap and readily available, which can significantly reduce the preparation cost, is green and environmentally friendly, and realizes the resource utilization of waste. The preparation method of the present invention is simple, easy to implement, and suitable for industrial production.

[0025] (2) The present invention uses ultrafine powder ceramsite powder as raw material, micron and nano graded polymer particles as pore formers, colloidal solution as binder, and prepares porous ceramsite with a multi-level cell structure through rotary granulation and nano spraying assistance, combined with heat treatment, which can achieve ultrafine particle size and a large number of micron and nanometer pores. The method of the present invention enables the size of the porous material of the present invention to be reduced to below 100 μm, and the application of wellbore heat insulation can prevent the ceramsite from being screened out by the solid-liquid separation device, which is conducive to multiple recycling; the porous material has a large number of micron and nanometer pores inside, with high porosity, low thermal conductivity, good insulation effect, and high strength.

[0026] (3) The present invention modifies the porous ceramsite into anions and cations so that it can adsorb onto the surface of the well wall with any charge, thereby achieving stable and effective heat insulation. DETAILED DESCRIPTION

[0027] The present invention will be further described below with reference to specific embodiments, but is not limited thereto.

[0028] Meanwhile, the experimental methods described in the following examples are conventional methods unless otherwise specified; the reagents and materials described are commercially available unless otherwise specified.

[0029] Example 1 A method for preparing a porous material for thermal insulation of a drilling wellbore comprises the following steps: (1) Fly ash, coal gangue, polypropylene micron particles and polystyrene nanoparticles are fully stirred and mixed in a round pot granulator to form a mixed powder. The mass ratio of fly ash, coal gangue, polypropylene micron particles and polystyrene nanoparticles is 1:1:0.3:0.1, the particle size of fly ash is 6-12μm, the particle size of coal gangue is 5-12μm, the particle size of polypropylene micron particles is 6-13μm, and the particle size of polystyrene nanoparticles is 100-500nm; (2) The mixed powder in step (1) is rotated in a round pot granulator, and a polyvinyl alcohol aqueous solution (Mw is 9000-10000) with a mass fraction of 0.5wt% is sprayed on the surface of the mixed powder with a nano sprayer during the rotation process. Under the action of gravity and rotation, the powder forms agglomerated microspheres, which are dried to obtain ceramsite microspheres. The rotation speed of the round pot granulator is 50r / min, the rotation time is 3min, the spraying speed of the nano sprayer is 80ml / min, and the mass ratio of the mixed powder to the polyvinyl alcohol aqueous solution is 1:0.05.

[0030] (3) heat treating the ceramsite microspheres in step (2) in a muffle furnace to obtain porous ceramsite, wherein the heat treatment temperature is 1300° C., the heat treatment time is 3 h, and the heat treatment atmosphere is air; (4) The porous ceramsite, 2-acrylamide-2-methylpropanesulfonic acid, dimethyldiallyl ammonium chloride and deionized water in step (3) are placed in a three-necked flask, oxygen is removed under a nitrogen atmosphere, and then a 3wt% aqueous solution of ammonium persulfate is added and stirred at 70°C for 8 hours. After the reaction is completed, the reaction product is washed with deionized water and then dried to obtain a porous material for drilling wellbore insulation. The mass ratio of the porous ceramsite, 2-acrylamide-2-methylpropanesulfonic acid, dimethyldiallyl ammonium chloride, deionized water and ammonium persulfate is 1:0.05:0.05:1:0.005.

[0031] The porous ceramsite prepared in this embodiment has a particle size of 60-80 μm; the thermal conductivity of the porous material is 0.045 W / m·k, the porosity is 85%, the compressive strength is 2.2 MPa, it has a multi-level cell structure, the pore size is 0.01-13 μm, and the surface carries both anions and cations.

[0032] Example 2 A method for preparing a porous material for thermal insulation of a drilling wellbore is as described in Example 1, except that the mass ratio of fly ash, coal gangue, polypropylene micron particles and polystyrene nanoparticles added in step (1) is 1:0.8:0.3:0.1. Other steps and conditions are the same as in Example 1.

[0033] The porous ceramsite prepared in this embodiment has a particle size of 60-80 μm; the thermal conductivity of the porous material is 0.041 W / m·k, the porosity is 86%, the compressive strength is 1.6 MPa, it has a multi-level cell structure, the pore size is 0.01-13 μm, and the surface carries both anions and cations.

[0034] Example 3 A method for preparing a porous material for heat insulation of a drilling wellbore is as described in Example 1, except that the mass ratio of fly ash, coal gangue, polypropylene micron particles and polystyrene nanoparticles added in step (1) is 1:0.5:0.3:0.1. Other steps and conditions are the same as in Example 1.

[0035] The porous ceramsite prepared in this embodiment has a particle size of 60-80 μm; the thermal conductivity of the porous material is 0.038 W / m·k, the porosity is 88%, the compressive strength is 1.3 MPa, it has a multi-level cell structure, the pore size is 0.01-13 μm, and the surface carries both anions and cations.

[0036] Example 4 A method for preparing a porous material for drilling wellbore insulation is as described in Example 1, except that in step (2), the rotation time of the rotary granulation is 5 minutes, and the other steps and conditions are the same as in Example 1.

[0037] The porous ceramsite prepared in this embodiment has a particle size of 70-90 μm; the thermal conductivity of the porous material is 0.040 W / m·k, the porosity is 87%, the compressive strength is 1.2 MPa, it has a multi-level cell structure, the pore size is 0.01-13 μm, and the surface carries both anions and cations.

[0038] Example 5 A method for preparing a porous material for thermal insulation of a drilling wellbore is as described in Example 1, except that in step (4), the mass ratio of porous ceramsite, 2-acrylamido-2-methylpropanesulfonic acid, dimethyldiallylammonium chloride, deionized water and ammonium persulfate is 1:0.01:0.005:1:0.005. The other steps and conditions are the same as those in Example 1.

[0039] The porous ceramsite prepared in this embodiment has a particle size of 60-80 μm; the thermal conductivity of the porous material is 0.044 W / m·k, the porosity is 86%, the compressive strength is 2.0 MPa, it has a multi-level cell structure, a pore size of 0.01-13 μm, and the surface carries both anions and cations.

[0040] Example 6 A method for preparing a porous material for thermal insulation of a drilling wellbore is as described in Example 1, except that in step (4), the mass ratio of porous ceramsite, 2-acrylamido-2-methylpropanesulfonic acid, dimethyldiallylammonium chloride, deionized water and ammonium persulfate is 1:0.1:0.1:1:0.005. The other steps and conditions are the same as those in Example 1.

[0041] The porous ceramsite prepared in this embodiment has a particle size of 60-80 μm; the thermal conductivity of the porous material is 0.048 W / m·k, the porosity is 82%, the compressive strength is 2.3 MPa, it has a multi-level cell structure, a pore size of 0.01-13 μm, and the surface carries both anions and cations.

[0042] Comparative Example 1 A method for preparing a porous material is as described in Example 1, except that the mass ratio of fly ash, coal gangue, polypropylene micron particles and polystyrene nanoparticles added in step (1) is 1:0.1:0.3:0.1. Other steps and conditions are the same as those in Example 1.

[0043] The particle size of the porous ceramsite prepared in this comparative example is 60~80μm; the thermal conductivity of the porous material is 0.027W / m·k, the porosity is 94%, it has a multi-level cell structure, the pore size is 0.01~13μm, and the surface carries both anions and cations; due to the low amount of coal gangue added, the reinforcing phase cannot be evenly infiltrated into the skeleton structure of the porous ceramsite material, resulting in a sharp decrease in compressive strength to only 0.5MPa.

[0044] Comparative Example 2 A method for preparing a porous material is as described in Example 1, except that the mass ratio of fly ash, coal gangue, polypropylene micron particles and polystyrene nanoparticles added in step (1) is 1:2:0.3:0.1. Other steps and conditions are the same as those in Example 1.

[0045] The porous ceramsite prepared in this comparative example has a particle size of 60-80 μm; the thermal conductivity of the porous material is 0.087 W / m·k, the porosity is 64%, it has a multi-level cell structure, the pore size is 0.5-10 μm, and the surface carries both anions and cations; due to the excessive amount of coal gangue added, a large amount of reinforcing phase penetrates into the skeleton structure of the porous ceramsite material, resulting in a decrease in porosity and pore size, and an increase in compressive strength to 5 MPa.

[0046] Comparative Example 3 A method for preparing a porous material is as described in Example 1, except that the mass fraction of the polyvinyl alcohol aqueous solution sprayed in step (2) is 1 wt%. The other steps and conditions are the same as in Example 1.

[0047] The porous ceramsite prepared in this comparative example has a particle size of 200-1000 μm; the thermal conductivity of the porous material is 0.065 W / m·k, the porosity is 73%, the compressive strength is 3 MPa, it has a multi-level cell structure, the pore size is 0.1-50 μm, and the surface carries both anions and cations; due to the increase in the mass fraction of the polyvinyl alcohol colloid solution, the viscosity of the nucleated particles increases during rotary granulation, and a large amount of free materials are adsorbed, resulting in an increase in the size and pore size of the porous ceramsite material and an increase in the thermal conductivity.

[0048] Comparative Example 4 A method for preparing a porous material, as described in Example 1, except that step (4) is not performed and the porous ceramsite is not modified.

[0049] The porous ceramsite prepared in this comparative example has a particle size of 60-80 μm; the thermal conductivity of the porous material is 0.043 W / m·k, the porosity is 87%, the compressive strength is 2.1 MPa, it has a multi-level cell structure, the pore size is 0.01-13 μm, and there are no anions and cations on the surface.

[0050] The particle size of the porous ceramsite in Examples 1-6 and Comparative Examples 1-4, the thermal conductivity, porosity, compressive strength and pore size indicators of the porous materials are shown in Table 1.

[0051] Table 1 Particle size, thermal conductivity, porosity, strength and pore size of porous materials As shown in Table 1, in the embodiment, as the amount of coal gangue decreases, the total mass proportion of the mixed powder also decreases, and the mass proportion of the pore-forming agent increases, which leads to an increase in the porosity of the porous ceramsite, a decrease in thermal conductivity and a decrease in strength. However, there is almost no effect on the particle size and pore size of the porous ceramsite. As the rotation time increases, the size of the ceramsite is also getting bigger, because in the continuous rotation process, new powder is continuously added to the ceramsite to make it larger, but the effect on the performance is not great. In Comparative Example 1, the mass of coal gangue is excessively reduced, resulting in an increase in the porosity of the prepared porous ceramsite and a decrease in thermal conductivity, but a serious decrease in strength. In Comparative Example 2, the mass of coal gangue is excessively increased, resulting in a decrease in the porosity of the prepared porous ceramsite and an increase in thermal conductivity, but a sharp increase in strength. In Comparative Example 3, the concentration of the colloidal solution is increased, resulting in an increase in the viscosity of the solution, and spraying on the mixed powder will bring up a large mass of powder into balls, resulting in an increase in size, density and strength. In Comparative Example 4, the porous ceramsite is not modified, the porosity of the porous ceramsite is slightly increased, and the thermal conductivity is increased.

[0052] Test Example 1 Study on thermal insulation properties of porous materials (1) preparing a base slurry, the components of which are water, bentonite and anhydrous sodium carbonate in a mass ratio of 100:2:1; (2) dispersing the porous material prepared in Examples 1-3 into the base slurry of step (1) to form a mud cake by filtration, wherein the mass ratios of the base slurry to the porous material are 1:0.005, 1:0.01 and 1:0.03 respectively; (3) placing the mud cake from step (2) on a heating table, heating at 200°C for 30 min, and observing the surface temperature of the mud cake with an infrared camera; The thermal insulation effects of pure mud cake without porous material and mud cake with porous material of different mass ratios are shown in Table 2 Table 2 Heat insulation effect of mud cake It can be seen from Table 2 that after adding porous materials, the mud cake formed has excellent thermal insulation performance, and with the increase of the amount of addition and the decrease of the thermal conductivity of the porous material, the temperature difference between the upper and lower parts of the mud cake also increases. This is mainly because the porous material is evenly distributed inside the mud cake, and its matrix structure is more complex than that of solid solids, which increases the heat conduction path, thus obtaining a larger temperature difference.

[0053] The above is only a specific implementation of the present invention, but the design concept of the present invention is not limited to this. Any non-substantial changes to the present invention using this concept shall be deemed as an act of infringing the scope of protection of the present invention. However, any simple modification, equivalent change and modification made to the above embodiments in any form according to the technical essence of the present invention without departing from the content of the technical solution of the present invention shall still fall within the scope of protection of the technical solution of the present invention.

Claims

1. A porous material for drilling wellbore insulation, characterized in that: The porous material is a spherical structure, with a thermal conductivity of 0.03 to 0.07 W / mk, a porosity of 80 to 95%, and a compressive strength of 1 to 3 MPa; the porous material has a multi-level cell structure with a pore size of 0.01 to 20 μm; and the surface of the porous material has anionic and cationic groups.

2. The porous material for drilling wellbore insulation according to claim 1, characterized in that: The porous material has a spherical structure, a thermal conductivity of 0.038 to 0.048 W / mk, a porosity of 82 to 88%, and a compressive strength of 1.2 to 2.3 MPa; the porous material has a multi-level cell structure, and a pore size of 0.01 to 13 μm; the surface of the porous material has anionic and cationic groups.

3. The method for preparing the porous material for drilling wellbore insulation according to claim 1 or 2, comprising the steps of: (1) Fully mixing ceramsite powder and pore-forming agent to obtain mixed powder; using colloidal solution as a binder, granulating to obtain ceramsite microspheres; and then heat treating to obtain porous ceramsite; The ceramsite powder is one or a combination of two or more of clay, shale powder, fly ash, coal gangue or iron tailings; the pore former is a combination of micron particles and nanoparticles, the micron particles are polypropylene, polyethylene or polystyrene micron particles, and the nanoparticles are polypropylene, polyethylene or polystyrene nanoparticles; the colloidal solution is one or a combination of two or more of polyvinyl alcohol aqueous solution, polyacrylamide aqueous solution or polyethylene glycol aqueous solution; (2) fully dispersing porous ceramsite, anionic monomers, and cationic monomers in deionized water, adding an initiator, reacting, and then washing and drying to obtain a porous material for drilling wellbore insulation; The anionic monomer is one or a combination of two or more selected from 2-acrylamido-2-methylpropanesulfonic acid, styrenesulfonate, ethylenesulfonate, propylenesulfonate, acrylic acid, methacrylic acid or hydroxyethylacrylic acid; the cationic monomer is one or a combination of two or more selected from dimethyldiallylammonium chloride, polyacrylammonium or polyquaternary ammonium salt; and the initiator is one or a combination of two or more selected from ammonium persulfate, sodium bisulfite or azobisisobutylimidazoline hydrochloride.

4. The method for preparing the porous material for drilling wellbore thermal insulation according to claim 3, characterized in that: In step (1), the ceramsite powder is a combination of fly ash and coal gangue; wherein the mass ratio of fly ash to coal gangue is 1:0.5-1.

5. The method for preparing the porous material for drilling wellbore heat insulation according to claim 3, characterized in that: In step (1), one or more of the following conditions are included: i. The particle size of ceramsite powder is 0.5~20μm; ii. In the pore-forming agent, the particle size of the micron particles is 6-13 μm, and the particle size of the nanoparticles is 100-500 nm; the mass ratio of the micron particles to the nanoparticles is 2-4:1; iii. The mass ratio of ceramsite powder to pore-forming agent is 3.75-5:1; iv. The mixing of ceramsite powder and pore-forming agent is carried out in a round pot granulator.

6. The method for preparing the porous material for drilling wellbore heat insulation according to claim 3, characterized in that: In step (1), one or more of the following conditions are included: i. The concentration of the colloidal solution is 0.1-0.8wt%; ii. The mass ratio of the mixed powder to the colloidal solution is 1:0.001-0.1; iii. Granulation is carried out in a round pot granulator; the mixed powder is rotated in the round pot granulator, and a colloidal solution is sprayed on the surface of the mixed powder with a nano sprayer during the rotation process. Under the action of gravity and rotation, the mixed powder forms agglomerated micron balls, which are dried to obtain ceramsite microspheres; wherein the rotation speed of the round pot granulator is 10 to 200 r / min, the rotation time is 2 to 10 min, and the spraying speed of the nano sprayer is 30 to 1000 ml / min; iv. The heat treatment temperature is 1000-1500°C, the heat treatment time is 2-10 hours, and the heat treatment atmosphere is air.

7. The method for preparing the porous material for drilling wellbore heat insulation according to claim 3, characterized in that: In step (2), the mass ratio of porous ceramsite, anionic monomer, cationic monomer, initiator and deionized water is 1: (0.01-0.1): (0.005-0.1): (0.005-0.01): (0.5-3).

8. The method for preparing the porous material for drilling wellbore heat insulation according to claim 3, characterized in that: In step (2), one or more of the following conditions are included: i. The initiator is in the form of an initiator aqueous solution, and the concentration of the initiator aqueous solution is 0.5-5wt%; ii. The reaction temperature is 20-80°C, the reaction time is 6-12h, and the reaction is carried out in the absence of oxygen, under protective gas protection and under stirring conditions.

9. The use of the porous material for drilling wellbore insulation as claimed in claim 1 or 2, characterized in that: As a thermal insulation material, it is used for thermal insulation of ultra-deep drilling wells.

10. The use of the porous material for thermal insulation of a drilling well according to claim 9, characterized in that: Ultra-deep layers are strata with a depth greater than or equal to 8000m.

Citation Information

Patent Citations

  • Heat insulation ceramsite wallboard

    CN114276084A

  • Yunnan laterite-based composite porous ceramsite as well as preparation method and application thereof

    CN118495983A

  • Inorganic heat-insulating material with three-level hole structure and preparation method of inorganic heat-insulating material

    CN103011882A

  • Light-weight, high-strength and low-thermal conductivity anorthite porous ceramic material and preparation method thereof

    CN109678478A

  • Preparation method of heat-preservation pipe shell material with micro-nano size and hierarchical pores

    CN112408938A

Cited By

  • Two-dimensional porous micron-sheet thermal insulation material for drilling fluid as well as preparation method and application thereof

    CN120329497A

  • A two-dimensional porous microparticle sheet heat insulation material for drilling fluid and a preparation method and application thereof

    CN120329497B